2022
DOI: 10.1007/s11748-022-01804-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of loop technique with ring annuloplasty: a > 10-year experience

Abstract: Objective:We assessed the long-term outcomes of the loop technique with ring annuloplasty for mitral regurgitation from our >10-year experience. Methods:We retrospectively reviewed 362 patients who underwent the loop technique with ring annuloplasty via median sternotomy or right mini-thoracotomy for mitral regurgitation. The median follow-up duration was 4.1 years (interquartile range, 2.3-5.8 years).Results: This study involved 147 women and 215 men (median age, 66.5 years). Mitral regurgitation was caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Some investigations have revealed that even mild residual MR after repair increases the chance of eventual repair failure necessitating reoperation. 3 , 5 , 9 , 15 However, no difference was found in the peak and average forces on the primary and secondary chordae between mild and perfect repair in our study. As described above, if there is some coaptation, secondary chordae are able to share the stress with primary chordae, minimizing the stress on both chords.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Some investigations have revealed that even mild residual MR after repair increases the chance of eventual repair failure necessitating reoperation. 3 , 5 , 9 , 15 However, no difference was found in the peak and average forces on the primary and secondary chordae between mild and perfect repair in our study. As described above, if there is some coaptation, secondary chordae are able to share the stress with primary chordae, minimizing the stress on both chords.…”
Section: Discussioncontrasting
confidence: 75%
“… 1 Residual postrepair MR has been a great concern and is known to influence mortality and induce adverse left ventricular (LV) remodeling, recurrence of significant MR, and reoperation. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Residual MR has been reported to be associated with recurrent severe MR resulting in reoperation, 2 , 4 , 6 , 8 , 10 even in mild cases. 3 , 5 , 9 , 14 In addition, the prevalence of significant MR after MV repair is relatively higher in anterior valve prolapse (AVP) repair compared with posterior valve prolapse repair.…”
mentioning
confidence: 99%